Interlayer vacancy defects in AA-stacked bilayer graphene: density functional theory predictions - Vuong, A.; Trevethan, T.; Latham, C. D.; Ewels, C. P.; Erbahar, D.; Briddon, P. R.; Rayson, M. J. (Iop Publishing Ltd, 2017)
AA-stacked graphite and closely related structures, where carbon atoms are located in registry in adjacent graphene layers, are a feature of graphitic systems including twisted and folded bilayer graphene, and turbostratic graphite. We present the results of ab initio density functional theory calculations performed to investigate the complexes that are formed from the binding of vacancy defects across neighbouring layers in AA-stacked bilayers. As with AB stacking, the carbon atoms surrounding lattice vacancies can form interlayer structures with sp(2) bonding that are lower in energy than in-plane reconstructions. The sp(2) interlayer bonding of adjacent multivacancy defects in registry creates a type of stable sp(2) bonded 'wormhole' or tunnel defect between the layers. We also identify a new class of 'mezzanine' structure characterised by sp(3) interlayer bonding, resembling a prismatic vacancy loop. The V-6 hexavacancy variant, where six sp(3) carbon atoms sit midway between two carbon layers and bond to both, is substantially more stable than any other vacancy aggregate in AA-stacked layers. Our focus is on vacancy generation and aggregation in the absence of extreme temperatures or intense beams.
Keywords: graphene; vacancy defect; density functional theory; radiation damage; wormhole; graphite